The location of innovative activity in Europe - Laura Abramovsky; Rachel Griffith; Gareth Macartney; Helen Miller (Institute for Fiscal Studies (IFS), 2008)
In this paper we use new data to describe how firms from 15 European countries organise their innovative activities. The data matches firm level accounting data with information on the patents that those firms and their subsidiaries have applied for at the European Patents Office. We describe the data in detail.
Keywords: F21; F23; O3; H3; 330; International investment and multinational firms; Technological Change and Research and Development; Fiscal Policies and Behaviour of Economic Agents; Innovationspolitik; Patent; Räumliche Verteilung; EU-Staaten